Mathematical Modeling for the Analysis and Optimization of Nutrient Dynamics in Edible Mushrooms (European Journal of Pure and Applied Mathematics, 2025)
Edible mushrooms are a valuable source of essential nutrients, including proteins, vitamins, minerals, and dietary fibers, making them important for human health and nutrition. Their nutrient composition varies with species, substrate type, and environmental conditions. This paper presents a mathematical model describing nutrient absorption, retention, and degradation in edible mushrooms using differential equations derived from controlled growth experiments. The model captures the dynamic interaction between substrate nutrients and mushroom metabolism, helping to identify key factors influencing nutrient accumulation. Parameter estimation and sensitivity analysis confirm the model’s accuracy in predicting nutrient variations across growth conditions. Simulation results reveal optimal environmental and substrate parameters that maximize nutrient content and overall yield. The proposed framework provides a quantitative approach to improving mushroom cultivation efficiency and nutritional value, offering potential applications in sustainable agriculture, food processing, and nutritional science.
Keywords: Edible mushroom; Essential nutrient; Human health; Mathematical model; Substrate composition